Pengaruh Learning Organization dan Innovation Strategy Terhadap Daya Saing Bawang Putih Di Kabupaten Temanggung - Arief Kurniawan; Ivan Yulivan; Jubaedah Jubaedah (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2020)
The problems faced in the development of garlic production in Temanggung regency are the competitiveness of garlic in Temanggung Regency is still low due to the inadequate ability of garlic farmers and institutions the garlic farmers group has not been able to create an Innovation Strategy through the use of technology in garlic cultivation. This research is a quantitative study to determine the effect of Learning Organization and Innovation Strategy on Garlic Competitiveness in Temanggung Regency. The study was conducted with a total sample of 73 farmer groups from 90 existing farmer groups in 3 garlic center districts namely Bulu District, Parakan District, and Kledung District. Data processing uses Structural Equation Modeling (SEM) analysis using the Partial Least Square (PLS) approach. The results of the analysis in this study indicate that (1) There is no direct influence of Learning Organization on Garlic Competitiveness, (2) there is a direct effect of Innovation Strategy on Garlic Competitiveness, (3) there is an indirect influence of Learning Organization on Garlic Competitiveness through Innovation Strategy, and (4) there is a direct influence of Learning Organizations on Innovation Strategy.Keywords: Learning Organization, Innovation Strategy, Competitiveness, and Garlic.ABSTRAKPermasalahan pengembangan produksi bawang putih di kabupaten Temanggung adalah daya saing bawang putih yang masih rendah. Hal ini disebabkan karena kemampuan petani bawang putih yang belum memadai dan kelembagaan kelompok petani bawang putih belum dapat menciptakan strategi inovasi dalam pemanfaatan teknologi budidaya bawang putih. Studi ini bertujuan untuk untuk mengetahui pengaruh Learning Organizationdan, Innovation Strategyterhadap daya saing bawang putihdi kabupaten Temanggung. Penelitian dilakukan dengan jumlah sampel sebanyak 73 kelompok tani dari 90 kelompok tani yang ada di 3 kecamatan sentra bawang putihyaitu kecamatanBulu, kecamatan Parakan, dan kecamatan Kledung. Anaisisdata menggunakan analisis Structural Equation Modelling (SEM) dengan  pendekatan Partial  Least  Square (PLS). Hasil analisis pada penelitian ini menunjukkan bahwa (1) tidak ada pengaruh langsung Learning Organization terhadap Daya Saing bawang putih, (2) terdapat pengaruh langsung Innovation Strategy terhadap daya saing budidaya bawang putih, (3) terdapat pengaruh tidak langsung Learning Organzation terhadap daya saingbudidaya bawang putihmelalui Innovation Strategy, dan (4) terdapat pengaruh langsung Learning Organization terhadap Innovation Strategy.Kata kunci:Organisasi Pembelajar, Strategi Inovasi, Daya Saing, dan Budidaya Bawang Putih